E-Module of Pancasila Education in the Independent Curriculum Based on Banyuwangi Local Wisdom for Grade IV Elementary School Students - Tasya Septhia Cahyani; Fajar Surya Hutama; Zetti Finali; Ervan Prasetyo; Moh Salimi (MIMBAR PGSD Undiksha, 2025)
The teaching materials used at elementary school are still ineffective and less engaging for students. This occurs because classroom teachers rely solely on textbooks as their main reference. This study aims to analyze the development process and evaluate the validity, effectiveness, and practicality of an e-module based on Banyuwangi's local wisdom to produce a high-quality learning medium. The product trial was conducted at elementary school with 10 students. The research subjects included 20 fourth-grade A students as the experimental class and 20 fourth-grade B students as the control class. The data collection instruments used were: (1) questionnaires, (2) learning outcome tests, (3) documentation.  The type of research used is research and development, referring to the Borg and Gall model. The validity of the product validation test, with a score of 92.5, meets the highly feasible criteria. The effectiveness test, with a relative score of 89.9%, meets the very high effectiveness criteria. The practicality test, based on student response questionnaires, scored 95.8, meeting the highly practical criteria. Based on these findings, the development of this e-module is valid, effective, and practical for use in learning activities. This development research has implications for classroom learning, making learning significantly more effective, as seen from the pretest and posttest results compared to the previously used teaching materials (textbooks). The relative effectiveness level of this e-module is 89.9%.